Penerapan Komunikasi SBAR dan Handover - Sulistiyani Sulistiyani; Jems KR Maay; Guruh Suprayitno; Dwi Sudaryanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to measure the application of SBAR and handover at the change of shifts in the inpatient room of the Merauke Hospital in Papua. The research method used is quantitative research with a cross-sectional research design. The results showed that most nurses were 40 years old, female, had 1-5 years of service, had Diploma III education, had never attended training, SBAR communication was inappropriate for 44 nurses, and the handover implementation was quite good. The P-value is 0.000 with a Spearman'Rho correlation coefficient of 0.783. In conclusion, a strong relationship exists between SBAR communication and the performance of acceptance weighing at Merauke Hospital, Papua. Keywords: Handover, SBAR Communication, Shift Change, Hospitalization